Pelatihan Pemasaran dan Pembukuan Keuangan dalam Mendapatkan Pembiayaan Bank Syariah bagi Pedagang Pasar Cileungsi - Novingky Ferdinand; Nurul Iman Maulana; Thoriq Aziz (Jurnal Pengabdian Masyarakat Madani, 2021)
The issue of non-bankable MSME entrepreneurs is often a very interesting issue because of the simple constraints of MSMEs in marketing and accounting for business finances. Along with the opening of banking access as widely as possible and the support of MSMEs to upgrade from the government, MSMEs must respond well to this problem. The purpose of implementing community service activities for the Cileungsi Market traders is to develop and improve the capabilities of the Cileungsi Market merchant community in terms of marketing and financial accounting. Also, the problem that is now the focus of this training is to improve the ability of MSMEs to carry out marketing and good financial accounting so that MSMEs become Bankable. The method used is to conduct marketing training and financial bookkeeping as a condition for obtaining financing at Islamic banks. From the results of the training, the traders were enthusiastic and committed to following up on this training to immediately make good marketing and financial accounting to apply for financing to Islamic Banks to develop their businesses.